Effects of fin structure size on methane-steam reforming for hydrogen production in a reactor heated by waste heat. (7th August 2020) - Zheng, Bin; Sun, Peng; Meng, Jian; Liu, Yongqi; Wang, Geoff; Tang, Shuai; Xu, Jiguo; Zhang, Kai
Abstract: This paper mainly describes the influence of changes in fin structure on the hydrogen production capacity of the methane-steam reforming system. The model of the triangular-fin-tube steam generator was set up. The effects of the fin height (34 mm–46 mm), fin root width (3 mm–6 mm) and the fin-type were studied. As the height of the fin increases (34 mm–46 mm), the CPC temperature at the outlet of the steam generator decreases (the maximum temperature decreases 23.6 K and the average temperature decreases 18.9 K). At the same time, the heat recovery efficiency increased from 96.3% to 98.4%, and so the system hydrogen production increases. As the fin root width increases (3 mm–6 mm), the CPC temperature at the outlet of the steam generator decreases (the maximum temperature decreases 3.7 K and the average temperature decreases 1.2 K). Meanwhile, the heat recovery efficiency increases from 97.5% to 98.1%, and so the system hydrogen production increases. When the fin type is changed from a straight fin to a triangular-fin, the average temperature of the solid particle decreases 30.5 K, the heat recovery efficiency increases by 7.9%, and the system hydrogen production increases.